SINTESIS DAN KARAKTERISASI SIFAT MEKANIK BIOKOMPOSIT FILLER SHORT FIBER KULIT ROTAN HASIL FERMENTASI - Atin A. Anggraeni (Jurnal Biofisika, 2012)
Rattan bark fiber as synthetic fiber at composite filler replacement has been used in this research. The extraction of the rattan bark fiber are done using a fermenta tion method of Aspergillus niger and milling.The fiber that created are long and short fiber (2 mm) in shape. Biocomposite synthesis using blending-hot press method that suitable with variant mechanical standardization test, ASTM D2240 for hard tools test, ASTM D1822 for pull tools test. Rattan bark fiber act as filler, polypropylene as matrix, and maleat acid as coupling agent. Mechanical measurement test of biocomposite sf (5%) and sm (5%) result shows that the hardest point are 4.33 ±0.17 Mpa. The sf (5%) and sm (5%) biocomposite pulling power are 140.12 ± 0.76 Mpa. Biocomposites filler short fiber rattan skin fermentation method has the potential to be further developed as a multi-functional materials.